SYSTEMATIC LITERATURE REVIEW: THE EFFECT OF AUDIT OPINION AND PROFITABILITY ON FIRM VALUE - Sri Widiyati; Netty Herawaty; Achmad Hizazi (Journal of Development Economics and Digitalization, Tourism Economics, 2026)
This systematic literature review examines the influence of Audit Opinion and Profitability on Firm Value, motivated by the necessity of enhancing market performance amid changing economic conditions. Utilizing the Systematic Literature Review (SLR) method, this study analyzed 16 open-access journal articles published between 2020 and 2025, sourced from Google Scholar using the keywords “audit opinion and profitability”. The synthesized findings reveal that the inconsistency in prior research is structurally driven by specific contextual and methodological boundaries. (1) The impact of an Audit Opinion on Firm Value is highly sensitive to industry classification; standard unqualified opinions serve as a baseline necessity for general sectors but are heavily discounted in sustainability-driven indices, while its direct effect is further diluted when firm size is factored in methodologically. (2) The relationship between Profitability and Firm Value is structurally shaped by geographic market maturity and internal risk controls. While frontier markets heavily rely on net earnings as a primary investment compass, modern investors in emerging markets evaluate profits contextually and penalize high earnings if paired with poor corporate governance or a lack of corporate social responsibility (CSR). (3) When tested collectively, Audit Opinion and Profitability provide a high-integrity, comprehensive information mapping that effectively dictates firm value by minimizing information asymmetry. Overall, this review concludes that firm value is a multidimensional construct, causing investors to evaluate both financial performance and information credibility simultaneously before making investment decisions.